Freddie vs. the family curse - Badua, Tracy (Clarion Books, 2022)
Freddie Ruiz suffers from a curse that has plagued his family for generations, so when he discovers a family heirloom, a century-old amulet from the Philippines that's supposed to bring good fortune, he thinks he'll finally be able to turn his luck around. But he soon learns that the spirit of his grumpy great-granduncle Ramon, the very one who'd brought the family curse upon them, is trapped in the heirloom, and Freddie and his cousin, Sharkey, have thirteen days to break the curse or else Freddie will die.